Microbiome-immune crosstalk in allergic rhinitis: lung and intestinal microbiota mechanisms - Wang, Chendong; Zhai, Chuntao; Hu, Shouxi; Lü, Yu’e (Frontiers in Microbiology, 2025)
Allergic rhinitis (AR) is a prevalent immune-mediated upper respiratory disorder that manifests as an itchy nose, nasal congestion, a runny nose, and other symptoms. Emerging research suggests that AR, beyond its IgE-mediated hypersensitivity, indirectly influences the immune system by altering the equilibrium of the lung and intestinal microbiota. Therefore, future research should systematically characterize the mechanistic involvement of the respiratory and intestinal microbiomes in AR development, which may reveal innovative therapeutic targets. This review highlights the mechanisms by which the lung and intestinal microbiota contribute to the pathogenesis of AR and discusses potential therapeutic strategies.